2015
DOI: 10.1007/s00436-015-4402-6
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic parasites in feces and fur of stray and private dogs from Italy

Abstract: The present study evaluated the occurrence of zoonotic parasites in feces and on fur of stray and private dogs living in Italy. Individual fecal samples collected from 117 and 385 kenneled (i.e., rescue shelter) and privately owned dogs, respectively, were examined by conventional copromicroscopy. Samples positive for Giardia duodenalis and Cryptosporidium spp. were subjected to further genetic characterization. Additionally, 174 fur samples of private and kenneled dogs living in the same area, 27 of which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
35
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 63 publications
10
35
3
Order By: Relevance
“…In our study, we found a higher overall prevalence of helminths than protozoa, similarly to what reported by Riggio et al (2013). G. duodenalis prevalence observed in the present study (21.4%) is high and confirms the findings of other recent studies both from Italy (Capelli et al 2006;Paoletti et al 2015) and from other European countries (Claerebout et al 2009;Epe et al 2010;Upjohn et al 2010). Probably, until recently, the real prevalence of this parasite in dogs was often underestimated (Capelli et al 2006), because of the low level of awareness of veterinarians through this parasite and the common use of less sensitive diagnostic techniques (Szwabe and Błaszkowska 2017), compared to the immunofluorescence kit adopted in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we found a higher overall prevalence of helminths than protozoa, similarly to what reported by Riggio et al (2013). G. duodenalis prevalence observed in the present study (21.4%) is high and confirms the findings of other recent studies both from Italy (Capelli et al 2006;Paoletti et al 2015) and from other European countries (Claerebout et al 2009;Epe et al 2010;Upjohn et al 2010). Probably, until recently, the real prevalence of this parasite in dogs was often underestimated (Capelli et al 2006), because of the low level of awareness of veterinarians through this parasite and the common use of less sensitive diagnostic techniques (Szwabe and Błaszkowska 2017), compared to the immunofluorescence kit adopted in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Previous surveys on dogs from the same study area reported a 76.5% (Berrilli et al 2004) and a 69.3% (Scaramozzino et al 2009) of dogspecific genotypes. Other studies in different Italian areas did not report any zoonotic assemblage (Paoletti et al 2015;Simonato et al, 2015).…”
Section: Discussionmentioning
confidence: 74%
“…The overall helminth prevalence recorded in the present survey (9.7%) is in agreement with data recently reported in restricted areas of central and northwestern Italy [29,30,32]. Moreover, single infections were more frequent than mixed infections, as already reported in other studies [26,40,41].…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of zoonotic helminths in owned dogs and the potential risks for human health have been worldwide investigated [25][26][27][28][29][30][31], but few surveys have been recently carried out in Italy [29,30,32]. Given the merit of a continuous update on parasite occurrence in dogs in contact with people, the present study evaluated the prevalence of zoonotic helminths in privately owned dogs from areas of central and north-eastern Italy where this info is outdated and incomplete [33].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the canid-specific assemblage C of G. duodenalis from the MC pack suggests a possible transmission between dogs and wild canids without public health concern. Indeed, the assemblages C appear to be strictly host specific and are commonly found in dogs (Ryan and Cacciò 2013;Paoletti et al 2015). To our knowledge, data relating the prevalence of Giardia spp.…”
Section: Discussionmentioning
confidence: 84%